2011
DOI: 10.1159/000325589
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Significance of the Number of Hours until Surgical Repair of Penile Fractures

Abstract: Objectives: We investigated whether a delay in time until surgery, in terms of hours, has any effect on the overall long-term results of surgical repair of penile fractures. Methods: Between 2001 and 2009, we operated on 56 patients with penile fractures. We evaluated 43 patients sorted into 3 groups according to the time interval until surgery. We applied the validated Turkish version of the International Index of Erectile Function (IIEF) questionnaire 3 times: for the time period before the fracture, 1 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…With regard to identifying characteristics of patients with true vs. false fracture, we noted that in our cohort, patients with confirmed penile fracture were generally younger and presented to the emergency department much sooner than those with a false fracture. Time from injury to operating suite did not seem to affect clinical outcome in our cohort, which is consistent with current literature regarding immediate vs. delayed fracture repair (Naraynsingh et al, 2003;Nasser & Mostafa, 2008;Yapanoglu et al, 2009;Kozacioglu et al, 2011). In fact, 22% of patients presenting within a day of injury had complications vs. 14% of those presenting more than a day from injury.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to identifying characteristics of patients with true vs. false fracture, we noted that in our cohort, patients with confirmed penile fracture were generally younger and presented to the emergency department much sooner than those with a false fracture. Time from injury to operating suite did not seem to affect clinical outcome in our cohort, which is consistent with current literature regarding immediate vs. delayed fracture repair (Naraynsingh et al, 2003;Nasser & Mostafa, 2008;Yapanoglu et al, 2009;Kozacioglu et al, 2011). In fact, 22% of patients presenting within a day of injury had complications vs. 14% of those presenting more than a day from injury.…”
Section: Discussionsupporting
confidence: 90%
“…1,8 However, recent studies have revealed that there is no serious deformity or erectile dysfunction as a consequence of delayed surgery in the long term in patients with no urethral involvement. In a study by Kozacioglu et al 9 of 56 patients with penile fracture, the mean time interval from trauma to surgery was 11.3 AE 8.5 h. Favourable outcomes of delayed surgery have also been noted by others. 10,11 In our case, surgical repair was offered more than 36 h after trauma due to the delayed presentation.…”
Section: S47mentioning
confidence: 75%
“…Our study demonstrates that delayed repair does not in any way affect the long term outcome in these patients. Kozacioglu and colleagues [23], reported no serious deformity or ED as a consequence of delay in surgery within a given time frame in 56 penile fractures, in terms of number of hours to presentation (mean number of hours from trauma to repair 11.3 ± 8.5 hours). Similarly , el-Assmy and colleagues [24], noted no difference in serious long-term complications between those who were treated surgically following an early (within 24 hours) or delayed (up to 7 days) presentation.…”
Section: Discussionmentioning
confidence: 96%